2006
DOI: 10.1002/app.25279
|View full text |Cite
|
Sign up to set email alerts
|

Binding properties of polyamidoamine dendrimers

Abstract: Dendrimers are globular, hyperbranched polymers possessing a high concentration of surface functional groups and internal cavities. These unique features make them good host molecules for small ligands. To reveal relationships between dendrimer size and its encapsulating properties, the interactions of the fourth and the sixth generations of polyamidoamine dendrimers (PAMAM G4 and PAMAM G6) with a fluorescent dye 1-anilinonaphthalene-8-sulfonate (ANS) were studied. Because ANS is a fluorescent molecule and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
(1 reference statement)
2
12
0
Order By: Relevance
“…In the case of 1,8-ANS in G6, the double reciprocal plot was linear, as shown in Figure 6c ); the fit results are listed in Table 3 . The value of K b obtained falls between the two values reported for 1,8-ANS in G6 in buffer solution by Bryszewska et al [ 25 ] for the low and high affinity binding centers. However the value of n obtained here is very small, and is expected to be much greater than 1 for this very large dendrimer [ 25 ].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In the case of 1,8-ANS in G6, the double reciprocal plot was linear, as shown in Figure 6c ); the fit results are listed in Table 3 . The value of K b obtained falls between the two values reported for 1,8-ANS in G6 in buffer solution by Bryszewska et al [ 25 ] for the low and high affinity binding centers. However the value of n obtained here is very small, and is expected to be much greater than 1 for this very large dendrimer [ 25 ].…”
Section: Resultssupporting
confidence: 83%
“…The results for the fits to Equation 3 are shown in Table 3 . For 1,8-ANS with G4, Bryszewska et al reported K b values of 5.6 × 10 4 M −1 [ 23 ], 2.6 × 10 5 M −1 (low affinity binding centers) and 3.7 × 10 6 M −1 (high affinity binding centers) [ 25 ] and n values of 0.31 [ 23 ], 0.60 (low affinity binding centers) and 0.34 (high affinity binding centers) [ 25 ] in buffer solution. Our value of K b of 1.8 ± 0.5 × 10 5 in nanopure water is in best agreement with that reported for the low affinity (surface) binding centers, however our value of n is slightly lower than that reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of dendrimers may be high because of their ability to sorb different substrates in different binding sites. Being derived from structural considerations [5], the presence of different binding sites in dendrimers was directly proved by 1 H NMR [6] and fluorescent [7] titration in solution. For dendrimers in solid state, this feature was concluded from dependence of guest uptake on their generation number [8] and from different adsorption kinetics for different substrates [9].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in fluorescence emission characteristics of fluorescence probes, e.g. 1‐anilinonapthalene‐8‐sulfonic acid, have been used to estimate binding constants . Several factors have been shown to influence the formation of dendrimeric complexes such as pH, molecular size, and surface structure [].…”
Section: Introductionmentioning
confidence: 99%